Doctoral students’ collaborative practices in developing writer identities - Tapia, Carla; Stewart, Nicola (Discourse and Writing/Rédactologie, 2022)
En route to their final thesis examinations, doctoral students face continuous challenges. These include institutional, instructional, personal, and social issues (Cotterall, 2011). These challenges can cause students to question their competency and ability to complete their programmes, despite any previous academic successes. Developing effective and productive writing habits may be the most demanding task facing research students. Academic writing is particularly challenging where students experience conflicts between their developing writer identities (Burgess & Ivanič, 2010) and the duties or responsibilities related to their lives outside the research programme: as carers; parents; or as new arrivals unfamiliar with the language and cultural conventions of a country or institution. We draw on Lave and Wenger’s (1991) description of Communities of Practice to outline the collaborative efforts undertaken by two doctoral students when developing their academic writing skills and writer identities. Both identify as immigrants to Australia: one has English as a second language; the other has returned to university (in a new country) after a 30-year hiatus. Developing academic writing identities has involved creating an English-speaking identity/self to overcome second language and cultural differences as well as to manage extensive challenges in terms of negotiation and navigation of academic writing practice genres. Although supervisors provide writing development guidelines, in this paper we focus on the nurturing support provided via the student community to overcome the different challenges presented during the PhD journey. Adopting an auto-ethnographical approach, we outline our individual challenges when developing writing identities and address the ways in which creating a collaborative support group has helped us improve writing style and productivity. It is in these circumstances – where individual needs extend beyond the readily available resources – that a peer-led community of practice can offer the necessary support and collaborative activities to enhance the learning experience of all participants. The group dynamics have evolved alongside developing writer identities as the nature of the support required changes over time and with experience. Creating this collaborative community has contributed to the development of wider-ranging linguistic, writing, technological, emotional, and social skills that extend above and beyond the remit of the PhD programme.